Increasing Production Capacity and Competitiveness of Bakery and Dairy SMEs in Babussalam Al-Firdaus Islamic Boarding School, Malang - Nurcholis, Mochamad; Nur, Mokhamad; Jatmiko, Yoga Dwi; Sriherfyna, Feronika Heppy; Maligan, Jaya Mahar; Rahayu, Aldila Putri (Journal of Innovation and Applied Technology, 2024)
Babussalam Al-Firdaus Islamic Boarding School is in Malang Regency, East Java.  Doktor Mengabdi (DM) activity involved Boarding School students diversifying dairy-based processed items and pastry products to start SMEs. Assistance and training are provided to increase product diversity, packaging design, production capacity, product selling value, SPP-IRT and halal certificate/label processing, and offline and online marketing to boost these business units' income. This effort allowed the DM team to test novel baked product recipes for DM partners. The DM team has also socialized and taught packaging design, SPP-IRT, halal certificates, and new product development materials. Partners have also learned to make wasant, cake, and sweet bread. The partner's NIB was gained this year.